PRODUCTIVE PERFORMANCE OF BROILERS REAREDON NEW LITTERS VS. REUSED LITTERS DURING FIVE FLOCKS - Vejarano R., María del Pilar (2008)
The aim of this study was to evaluate the performance and sanitary status of broilers chickens raised in new and reused litters. For this purpose, 125 male broilers from the Ross 308 line were raised in a new and 125 in a litter that has been reused during 5 flocks. Growth data was weekly collected, as well as ammonia levels, oocysts count per gram of litter, and count of coliformis bacteria, fungi and mesofilic bacteria (CFU per gram of litter)in both groups. Level of antibodies against infectious bronchitis, Newcastle disease, infectious bursal disease, chicken anemia virus, and avian reoviruses were evaluated by ELISA test at the beginning and ending of the flock (day 49). No statistical difference was found between groups on growth rate, ammonia levels and oocysts count, however, the CFU count for mesofilic bacteria was higher in birds on new litter (p<0.05). The serology results did not show any seroconversion to the analyzed virus. Based on the results, it would be expected that litters coming from poultry farms without a history of infectious problems and with an adequate handling of environmental conditions in the farm could be safely reused for up to 5 flocks.